Ahkamu Wilayati al-Mar'ah wa Abna'iha - Adeel Syabab (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2022)
The current study dealt with the issue of the women’s guardianship over their underage children, in which it was found that the woman (the mother) has the legitimate and legal right of guardianship on her non-adult children. The study also dealt with the variance in the arrangement and order of guardianship. For instance, in Islamic jurisprudence, the mother’s rank in guardianship order came after the father and grandfather,but before the guardian. Nevertheless, in the Algerian legislation, the mother was classified directly after the father. This research also came to a conclusion that the guardianship should be transferred to the mother if the father dies. Otherwise, in the case of the father’s absence or any other impediment, the mother takes in charge only the urgent matters of her children.